Organic Leaf Fertilizer Application to Increase Jabon Seedling Growth (Anthocephalus cadamba Roxb. Miq.) - Arum Sekar Wulandari; Sri Susanti (Jurnal Silvikultur Tropika, 2012)
Good seedlings  have good genetic quality and physical appearance such high, diameter, age, fresh leaves, free from pests and diseases. One way to get good quality seedling  throughs fertilizing. Research aims to know response of Jabon seedling growth which  is  given organic  leaf fertilizer. Research is done in the greenhouse by using  complete random design (RAL). Treatment which is given on jabon seedlings was granting organic leaf fertilizer, namely: fertilizer X, super-O, Saputra, and Agrobost. As control, jabon seedlings not given organic leaf fertilizer. The observed variables are the seedlings high, stem diameter, wet weight of shoots and roots, shoots and root dry weight ratio tops, roots, and root length. The results showed from 9 variables observed there are 7 variables that influence on   growth of the  jabon seedling, such as: high, diameter, heavy wet shoots and root dry weight, shoot and  roots. The granting of organic  leaf fertilizer Saputra gives a better growth than other treatments in terms of high growth that is 21.38 cm (nearly 15.34%), diameter is 3.59 mm (increase  36.59%), wet weight of shoots weighing nearly 18.78 g (increase  26.90%), heavy wet roots weighing is 7.74 g (increase 68.82%), dry weight of shoots is 3.13 g (nearly 93.17%) root dry weight, weighing  1.91 g (increase 117.16%). Seedling control and seedling treatment had NPA between 1.54-2.23. Seedlings jabon on all treatments have a long the same root, but it has a number of different roots. Jabon seedlings on all the treatments have a long the same root, but it has a number of different roots. The seeds are sprayed with organic leaf fertilizers have quality index value of  seedings > 0.09, meaning seed jabon can survive if moved to the field.